Social Media Communication Strategy of Al-Izzah Campus Da'wah Institute UIN North Sumatra in Optimizing the Spread of Islamic Values on Social Media - Sitorus, Ari Oldwin; Khatibah, Khatibah (Journal La Sociale, 2024)
This research aims to investigate how the communication strategy of the Al-Izzah UIN North Sumatra Campus Da'wah Institute (LDK) maximises the dissemination of Islamic ideals on social media. The research employed a descriptive qualitative research method. Qualitative research methods employ scientific techniques to elucidate a phenomenon by comprehensively summarising data and facts using language, with respect to the subject of study. The data collecting methods employed were interviews and observations of dakwah content on the LDK Al-Izzah UINSU Instagram social media account. The research incorporates the theories of New media proposed by Pierre Levy, the impact of dakwah on social media, and communication methods utilising SWOT analysis. The primary findings of this study reveal the effectiveness of utilising distinctive and innovative dakwah content, such as humorous videos, to captivate and engage the audience in the dakwah message. Furthermore, the deficiency in disseminating dakwah content on social media stems from a scarcity of manpower and the utilisation of rudimentary instruments for making dakwah content, hence leading to subpar outcomes in the created dakwah video content. Furthermore, there are potential to disseminate Islamic ideals on social media platforms, particularly through the emerging trend of providing innovative and contemporary preaching content. Furthermore, the Al-Izzah Campus Da'wah Institute faces a hindrance in disseminating Islamic ideals on social media due to the removal of parts of their dakwah content on LDK Al-Izzah's social media platforms.